2021
DOI: 10.21448/ijsm.989436
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant activities of essential oils and extracts from cones of Tetraclinis articulata (Vahl) Masters

Abstract: This study was carried out to evaluate the in vitro antioxidant activity and the chemical composition of essential oils and organic extracts of Moroccan Tetraclinis articulata cones (Khemisset region). The GC–MS analysis of essential oils identified a total 23 volatile components. The major constituents of the oil were α-pinene (18.33%), cis-verbenone (10.02%), and L-pinocarveol (8. 32%). For phytosterols analysis of hexane extract, β-sitosterol constitutes the majority with a percentage of 77.74%. The amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Despites rich literature about the plant, the chemistry and biology of T. articulata have yet to be thoroughly examined. For instance, the phytochemical screening of T. articulata cones methanolic extract has positively identified other classes of compounds such as alkaloids and saponosides ( Saber et al, 2021 ). Likewise, the individual compounds and their pharmacological effects have yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Despites rich literature about the plant, the chemistry and biology of T. articulata have yet to be thoroughly examined. For instance, the phytochemical screening of T. articulata cones methanolic extract has positively identified other classes of compounds such as alkaloids and saponosides ( Saber et al, 2021 ). Likewise, the individual compounds and their pharmacological effects have yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Aromatic plants currently present a reliable source of active ingredients known for their therapeutic properties, in particular, antioxidant activity (Saber et al, 2021). In this context, a study recently published under the theme, of ethnobotanical, phytochemical, and antioxidant study of fifty medicinal and aromatic plants, the results obtained can be considered as a source of information for scientific research in the field of pharmacology and phytochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, despite the development of modern medicine, aromatic plants remain a solid base that we cannot do without in our daily lives due to their various uses in different fields, as we have shown in this study for the three most used aromatic and medicinal plants by the rural population: Rosmarinus officinalis, Thymus vulgaris and Mentha pulegium. Importantly, the identification and quantification of secondary metabolites in different plant species is important for the discovery of new drugs and the development of herbal medicines, which is confirmed by earlier studies [25,29].…”
Section: • Thymus Vulgarismentioning
confidence: 58%
“…However, in the third year of our study, we observed a decline in essential oil production as the weather conditions continued to deteriorate for the sample of three plants. Additionally, other studies [24,25] have shown that the relative water content, chlorophyll index, and essential oil yield decreased under severe water deprivation. Moreover, Thymus vulgaris exhibited the highest yield of essential oil, followed by Rosmarinus officinalis, and finally Mentha pulegium.…”
Section: Essential Oilmentioning
confidence: 90%